Tanfīżu Istirātījiyyati Mubārāti Biṭāqati al-Fahrasi li Tarqiyati Natāiji Ansyiṭati Ta’līmi al-Lugati al-`Arabiyyati bi al-Madrasati - Dedi Mulyanto; Febriansyah Harma; Muhammad Nadzif Safwan Bin Abu Bakar (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2022)
The objectives of this study are divided into two things: a) to increase the learning activeness and b) to improve the learning outcomes of class 1A students using the index card match learning strategy in Arabic lessons at the KH. Syamsuddin durisawo ponorogo Islamic boarding school. This type of research is called "Classroom Action Research." This method has a significant influence on student activity. It improves student learning outcomes in Arabic lessons, and the number of students in class 1A is 28. This research aims to apply the index card match learning strategy to increase students' activeness and learning outcomes in Arabic subjects. Researchers used testing, observation, and documentation methods to obtain the necessary data. The research results are as follows: 1. The application of the index card match has achieved learning activeness in about 46% of 28 students, and the second stage of student activeness reaches 70% of 28 students. 2. The index card match strategy has achieved the learning outcomes. The student's score reaches 57%, and in the second stage, the student's score reaches 100% of the 28 students.